2007
DOI: 10.1152/ajpregu.00485.2007
|View full text |Cite
|
Sign up to set email alerts
|

Renal sympathetic nerve activity modulates afferent renal nerve activity by PGE2-dependent activation of α1- and α2-adrenoceptors on renal sensory nerve fibers

Abstract: Kopp UC, Cicha MZ, Smith LA, Mulder J, Hö kfelt T. Renal sympathetic nerve activity modulates afferent renal nerve activity by PGE 2-dependent activation of ␣1-and ␣2-adrenoceptors on renal sensory nerve fibers. Am J Physiol Regul Integr Comp Physiol 293: R1561-R1572, 2007. First published August 15, 2007; doi:10.1152/ajpregu.00485.2007.-Increasing efferent renal sympathetic nerve activity (ERSNA) increases afferent renal nerve activity (ARNA). To test whether the ERSNA-induced increases in ARNA involved nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
99
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 58 publications
(114 reference statements)
3
99
1
Order By: Relevance
“…The persistence of hypertensive blood pressure (BP) in patients with resistant hypertension is partially regulated by the renal sympathetic nerve system. [17][18][19][20][21] Renal sympathetic denervation (RSD) is an interventional treatment option for patients who have resistant hypertension, despite optimal medical treatment. 22,23 However, RSD is not effective in ≈8% to 12% of treated patients.…”
mentioning
confidence: 99%
“…The persistence of hypertensive blood pressure (BP) in patients with resistant hypertension is partially regulated by the renal sympathetic nerve system. [17][18][19][20][21] Renal sympathetic denervation (RSD) is an interventional treatment option for patients who have resistant hypertension, despite optimal medical treatment. 22,23 However, RSD is not effective in ≈8% to 12% of treated patients.…”
mentioning
confidence: 99%
“…1 Not only do increases in ARNA decrease ERSNA but also reflex increases in ERSNA increase ARNA. 2,3 The increased ARNA will, in turn, decrease ERSNA via activation of the renorenal reflexes, a negative-feedback mechanism, to maintain low-level ERSNA.Changes in ERSNA modulate ARNA by the release of norepinephrine (NE), which activates ␣ 1 -adrenoceptors (ARs) and ␣ 2 -ARs on renal sensory nerves, leading to increases and decreases in ARNA, respectively. 2 The physiologic importance of the ERSNA-induced increases in ARNA is underlined by the interaction being modulated by dietary sodium.…”
mentioning
confidence: 99%
“…1 The kidney also has abundant afferent sensory innervation, located primarily in the renal pelvic wall. 2,3 Sympathetic efferent nerve fibers and afferent sensory nerve fibers often run separately but intertwined in the same nerve bundles in the renal pelvic wall, 2 providing anatomic support for a functional interaction between efferent renal sympathetic nerve activity (ERSNA) and afferent renal nerve activity (ARNA). In normotensive rats, activation of the renal sensory nerves leads to decreases in ERSNA and natriuresis, an inhibitory renorenal reflex response.…”
mentioning
confidence: 99%
“…37 We recently reported that noradrenaline, released 38 from sympathetic vasomotor neurons or produced 39 locally in the epidermis, may augment inflammation after 40 distal tibia fracture by activating keratinocytes or 41 vascular endothelial cells (Li et al, 2013). In particular, (Hong and Abbott, 1996;Ali 54 et al, 1999;Nam et al, 2000;Hord et al, 2001;Xie 55 et al, 2001;Kim et al, 2005;Dogrul et al, 2006;Maruo 56 et al, 2006;Kopp et al, 2007;Meisner et al, 2007;57 Trevisani et al, 2007;Gibbs et al, 2008;Dawson et al, 58 2011;Donello et al, 2011). Notably, we recently reported 59 that a 1 -AR expression increased in dermal nerve bundles 60 4-28 days after partial sciatic nerve lesion (Drummond 61 et al, 2014b), and on nociceptive nerve fibers and kerati-62 nocytes 7 days after chronic constriction injury of the sci-63 atic nerve (Drummond et al, 2014a).…”
mentioning
confidence: 99%